The Comparison Between Recognition to Choice of Law in International Contracts by Courts and Arbitration in Indonesia - Susanti, Laras (Kertha Patrika; Vol 41 No 3 (2019), 2019)
Rapid international commerce leads to the significant use of international contracts. As parties coming from different legal systems, parties’ choice of law is essential. This article analyzes governance of choice of law in Indonesia legal framework and performance of courts in giving recognition to the choice of law. Using a normative approach, this article finds that Indonesia does have a lacking legal framework on the choice of law. Indonesia must rely on Article 18 General Rule on Regulations for Indonesia (Alegmene Bepaligen van Wetgeving voor Indonesia /AB) which only offers lex loci actus. Consequently, courts in Indonesia have decided on the choice of law inconsistently. In contrast, it is found that in Indonesia, the BANI Arbitration Center has clearer governance of the issue. The governance by the Center might be used to develop a better governance aimed to courts in Indonesia.